Emerging therapies in rheumatoid arthritis: focus on monoclonal antibodies - Senolt, Ladislav (F1000Research, 2019)
Advances in the treatment of rheumatoid arthritis (RA) are attributed to several aspects such as new classification criteria enabling early diagnosis and intensive treatment with the application of treat-to-target principles as well as better understanding of the pathogenesis of RA contributing to the development of targeted therapies. However, reaching remission is still not achieved in most patients with RA, which is one of the driving forces behind the continuous development of novel therapies and the optimization of therapeutic strategies. This review will outline several new therapeutic antibodies modulating anti-inflammatory cytokines interleukin (IL)-2 and IL-10 and pro-inflammatory mediators granulocyte-macrophage colony-stimulating factor, fractalkine, and IL-6 that are in various stages of clinical development as well as the progress in manufacturing biotechnologies contributing to the next generation of antibodies and their potential to expand the therapeutic armamentarium for RA. In addition, the fate of unsuccessful therapies including agents targeting IL-15, the IL-20 family, IL-21, chemokine CXCL10, B-cell activating factor (BAFF), and regulatory T (Treg) cells or a novel concept targeting synovial fibroblasts via cadherin-11 will be discussed.
Keywords: biological therapies; therapeutic strategies; cytokiny; Antibodies, Monoclonal; monoclonal antibodies; monoklonální protilátky; lidé; Arthritis, Rheumatoid; Cytokines; revmatoidní artritida; fibroblasty; rheumatoid arthritis; Fibroblasts; Humans